(3OQGSGJ aj GdUMGaI GdQjGVjI (B:s (3JZWjI GdeHGQjGJ GdQjGVjI UMajG GOGYjG h JdaRjhfjG JMQjQ GdGNHGQ GdQjGVjI (B/s - (3GOjH NVhQ s ((3OeTb (B:s (3GOjH NVhQ ,s, 1990)
(3GUHMJ GdUMGaI GdeJNUUI hGMOI ef SeGJ GdYUQ hHQRJ GdUMGaI GdQjGVjI HJWhdQ GdYGUa,dJhGcH GdJWhQ GdMGUd Ydi GdSGMI GdQjGVjI ,haj GdMjGI GdQjGVjI (B.(3hJQcRJ GdLghO h GdGHMGK h GdOQGSGJ dhVY GdGSGS GdUMaj GdYdej ddUMGaI GdQjGVjI GdeJNUUIs
Keywords: (3GdQjGVI h GdUMGaI GdQjGVjI (B/(3GdGNHGQ GdQjGVjI s